THE POWER OF WEB-GAMES : IMPROVING STUDENTS’ VOCABULARY MASTERY IN A FUN WAY - Dini Fitriani, Ajeng; Nafisatur Rizkia, Suci (Journal of English Education and Teacher Trainer, 2024)
The usage of the web application "WordWall Games" as a tool for learning vocabulary is examined in this article. The purpose of the study is to assess the participants' capacity for improving their vocabulary memorization, sentence construction, and pronunciation. Three research questions are addressed in this study: How does WordWall game design help students grow their vocabulary? How does WordWall gaming application fit into vocabulary education? How do students learn new words after using WordWall as a teaching tool? Ten Senior High School students at Academica Education Learning Course who were study participants were directly observed by the researchers in order to gather data for this study. The following six game-based media were used: anagram tasks, translation tasks, true-or-false tasks, crossword games, random card games, and construct word tasks. The study's conclusions show that employing WordWall games as a teaching aid helps students' memory, sentence structure, and pronunciation.